Reduced occurrence of ventilator-associated pneumonia after cardiac surgery using preoperative 0.2% chlorhexidine oral rinse: results from a single-centre single-blinded randomized trial. Issue 4 (December 2015) - Lin, Y.J.; Xu, L.; Huang, X.Z.; Jiang, F.; Li, S.L.; Lin, F.; Ye, Q.Y.; Chen, M.L.; Lin, J.L.
Summary: Since mechanical ventilation after cardiac surgery increases the risk of ventilator-associated pneumonia (VAP), we conducted a prospective randomized controlled trial to investigate the effect of preoperative 0.2% chlorhexidine on postoperative VAP. Ninety-four patients scheduled for heart surgery were randomized to a chlorhexidine group ( N  = 47) or control (saline) group ( N  = 47). On the day before surgery, patients gargled three times with 0.2% chlorhexidine or saline 30 min after each meal and 5 min after teeth brushing at bedtime. VAP occurred in 8.5% of the chlorhexidine group and in 23.4% of the controls. Preoperative chlorhexidine mouthwash reduced the incidence of postoperative VAP significantly.